Thermal diffusivity measurement of SnO2-CuO ceramic at room temperature - Mas’ut, Aiza Masyati; Abdul Wahab, Zaidan; Mat Yunus, Wan Mahmood; Edros, Norfarezah Hanim (Universiti Putra Malaysia Press, 2008)
Thermal diffusivity is a measure of rapidity of heat propagation through a material. The property is important in the understanding of gas sensor performance. Photoflash technique was used to determine thermal diffusivity of SnO2-based materials with varying amount of CuO ranging from 10 to 50 mol%, at room temperature. The samples were made disc-shaped, 10 mm in diameter with thickness ranging from 2.4 to 2.8 mm. We found that the thermal diffusivity values of SnO2-CuO samples ranging from 6.21 to 7.51Ã—10-2 cm2z-1 were better than the reported thermal diffusivity value of pure SnO2 sample (1.45Ã—10-2 cm2Z-1). The thermal diffusivity behaviour was supported by results from XRD and SEM.